Perceptions of PR: A Semiotic Analysis of The "Samantha Syndrome" and its Impact on Indonesian Female Public Relations Students - Laras Khairunnisa (Communicare : Journal of Communication Studies, 2022)
This research analyzed the character Samantha Jones from Sex and the City which created a phenomenon called “Samantha Syndrome”. “Samantha Syndrome” is defined as the misrepresentation of Public Relations as a glamorous job caused by Samantha Jones character. This paper examines how “Samantha Syndrome” applies to Indonesian female Public Relations students, using Stuart Hall’s Cultural Studies, also Charles Peirce’s semiotics approach. Analytical units for this research is scenes or clips from Sex and the City the movies that show the Samantha Jones’ portrayal and behaviors as a Public Relations Executive, that leads to Samantha Syndrome based on Jane Johnston’s findings. The scenes taken from online movie streaming website Netflix. To deepen the analysis, eight Indonesian female Public Relations students were interviewed to get their perspectives deeply about how The Samantha Syndrome theory implications to Indonesian female PR students towards their chosen profession.